2015
DOI: 10.17305/bjbms.2016.830
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum lipids and oxidative stress in patients with normal tension glaucoma, but not pseudoexfoliative glaucoma

Abstract: This study entailed a cross-examination of oxidant/antioxidant balance, high-density lipoprotein (HDL)-linked paraoxonase 1 (PON1) phenotypes, and levels of serum routine lipids among patients with normal tension glaucoma (NTG) or pseudoexfoliative glaucoma (PEXG) compared with healthy control groups. We aimed to investigate the links between oxidative stress (OS), HDL-related antioxidant enzyme activities and dyslipidemia in distinct subtypes of glaucoma. The study included 32 patients with NTG, 31 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Furthermore, Tang et al ( 18 ) showed that TRIG were higher, and was an independent risk factor for POAG. Other studies have also confirmed the association between LDL-C and glaucoma ( 9 , 19 ). Yilmaz et al ( 9 ) also found increased TRIG and CHOL levels in normal intraocular pressure glaucoma.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, Tang et al ( 18 ) showed that TRIG were higher, and was an independent risk factor for POAG. Other studies have also confirmed the association between LDL-C and glaucoma ( 9 , 19 ). Yilmaz et al ( 9 ) also found increased TRIG and CHOL levels in normal intraocular pressure glaucoma.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies have also confirmed the association between LDL-C and glaucoma ( 9 , 19 ). Yilmaz et al ( 9 ) also found increased TRIG and CHOL levels in normal intraocular pressure glaucoma. Lee et al ( 20 ) found that hyperlipidemia had a certain correlation with the occurrence and development of POAG.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Vacuolar protein sorting‐associated protein 4A (VPS4A) is also connected to the lipid transport according to the STRING network. Although the precise effects of these proteins on the ocular surface are still unknown, high level of high‐density lipoprotein (HDL) cholesterol ratio has been shown to reduce the likelihood of dry eye disease (Moss et al 2000), while hyperlipidemia, that is increased low‐density lipoprotein and decreased HDL levels in blood, has been associated with an increased risk of glaucoma and increased IOP (Yilmaz et al 2016, reviewed by Wang & Bao 2019). However, levels of lipid transporting proteins have not been previously examined from tear fluid in relation to glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that statins, which are medications used to lower cholesterol in patients with hyperlipidemia, may have some protection against glaucoma [3] , but it is still inconsistent on whether or not statins are beneficial in patients with glaucoma [2,4,5] .…”
Section: Disclosure Statementmentioning
confidence: 99%